Implementasi Shared Session Dalam Klaster Server Web Menggunakan PHP dan MySQL - R. Moch Makruf Puja Pradana; Mahendra Data; Dany Primanita Kartikasari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Session is a method that used to store information on a computer server that can be used on several pages including the page itself. In using a web server cluster, it can produce a better performance than using a single server that handles a website. But there are some problems that arise in the development between the web server cluster against the use of the session itself. In a web server cluster is a represented by a single node will run independently, if the initial session formed in the web application only have one node server, then the other server nodes can't get the same session access. The solution that can be used is to save the data session into database with mySQL, and the access of data session can be shared to another web servers. Another problem was revealed is how one web server cluster can communicate with the database in storing dan requesting data sessions. With these problems, this study developed the Shared Session method that will be applied through PHP. To prove that the method can run the system according to function, two tests are applied, login and logout testing and black box testing. In testing the login and logout that is designed can be fulfilled in storing and sharing data sessions even though there is a condition of one disabled web server. In the black box testing the response time results obtained in each scenario, in the first scenario of 100 session requests produces a response time of 18.7 second to 26.2 second, in the second scenario of 200 session requests produces a response time of 1 minutes up to 1.38 minutes, in the third scenario of 300 session requests to produce a response time of 10.07 seconds to 15.25 seconds.